Atypicalities in sleep and semantic consolidation in autism. Issue 3 (20th October 2019) - Fletcher, Fay E.; Knowland, Victoria; Walker, Sarah; Gaskell, M. Gareth; Norbury, Courtenay; Henderson, Lisa M.
Abstract: Sleep is known to support the neocortical consolidation of declarative memory, including the acquisition of new language. Autism spectrum disorder (ASD) is often characterized by both sleep and language learning difficulties, but few studies have explored a potential connection between the two. Here, 54 children with and without ASD (matched on age, nonverbal ability and vocabulary) were taught nine rare animal names (e.g., pipa). Memory was assessed via definitions, naming and speeded semantic decision tasks immediately after learning (pre‐sleep), the next day (post‐sleep, with a night of polysomnography between pre‐ and post‐sleep tests) and roughly 1 month later (follow‐up). Both groups showed comparable performance at pre‐test and similar levels of overnight change on all tasks; but at follow‐up children with ASD showed significantly greater forgetting of the unique features of the new animals (e.g., pipa is a flat frog). Children with ASD had significantly lower central non‐rapid eye movement (NREM) sigma power. Associations between spindle properties and overnight changes in speeded semantic decisions differed by group. For the TD group, spindle duration predicted overnight changes in responses to novel animals but not familiar animals, reinforcing a role for sleep in the stabilization of new semantic knowledge. For the ASD group, sigma power and spindle duration were associated with improvements in responses to novel and particularly familiar animals, perhaps reflecting more general sleep‐associated improvements in task performance. Plausibly, microstructural sleep atypicalities in children with ASD and differences in how information is prioritized for consolidation may lead to cumulative consolidation difficulties, compromising the quality of newly formed semantic representations in long‐term memory. Abstract : This polysomnography study examined the sleep‐associated consolidation of words for real but rare animals, in children with and without autism. Children with autism showed increased forgetting of novel features (e.g., an asp is a hairy caterpillar), relative to typical peers, one month after exposure. They also showed reduced sigma power (within the sleep spindle frequency range), and showed more general associations between overnight changes in task performance (for both novel and particularly familiar words) and sleep spindle parameters, in stark contrast to typical peers who showed selective associations between spindles and overnight changes in novel memory traces.